Cattle Tick Rhipicephalus microplus-Host Interface: A Review of Resistant and Susceptible Host Responses - Tabor, Ala E.; Ali, Abid; Rehman, Gauhar; Rocha Garcia, Gustavo; Zangirolamo, Amanda Fonseca; Malardo, Thiago; Jonsson, Nicholas N. (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks are able to transmit tick-borne infectious agents to vertebrate hosts which cause major constraints to public and livestock health. The costs associated with mortality, relapse, treatments, and decreased production yields are economically significant. Ticks adapted to a hematophagous existence after the vertebrate hemostatic system evolved into a multi-layered defense system against foreign invasion (pathogens and ectoparasites), blood loss, and immune responses. Subsequently, ticks evolved by developing an ability to suppress the vertebrate host immune system with a devastating impact particularly for exotic and crossbred cattle. Host genetics defines the immune responsiveness against ticks and tick-borne pathogens. To gain an insight into the naturally acquired resistant and susceptible cattle breed against ticks, studies have been conducted comparing the incidence of tick infestation on bovine hosts from divergent genetic backgrounds. It is well-documented that purebred and crossbred Bos taurus indicus cattle are more resistant to ticks and tick-borne pathogens compared to purebred European Bos taurus taurus cattle. Genetic studies identifying Quantitative Trait Loci markers using microsatellites and SNPs have been inconsistent with very low percentages relating phenotypic variation with tick infestation. Several skin gene expression and immunological studies have been undertaken using different breeds, different samples (peripheral blood, skin with tick feeding), infestation protocols and geographic environments. Susceptible breeds were commonly found to be associated with the increased expression of toll like receptors, MHC Class II, calcium binding proteins, and complement factors with an increased presence of neutrophils in the skin following tick feeding. Resistant breeds had higher levels of T cells present in the skin prior to tick infestation and thus seem to respond to ticks more efficiently. The skin of resistant breeds also contained higher numbers of eosinophils, mast cells and basophils with up-regulated proteases, cathepsins, keratins, collagens and extracellular matrix proteins in response to feeding ticks. Here we review immunological and molecular determinants that explore the cattle tick Rhipicephalus microplus-host resistance phenomenon as well as contemplating new insights and future directions to study tick resistance and susceptibility, in order to facilitate interventions for tick control.